We share the same struggle. Women in wales. Women in Nicaragua / Patricia Daniel - Daniel, Patricia (1998)
Why links between wales and the Atlantic Coast of Nicaruguan?, women all over striving for more participation, anyting is possible if your put your mind to it, Nicaraguan rite of passage, break the silence, say ´no´ to violence, enterprise and community, women in the countryside, country without language, country without heart, unity in deversity networking